Dynamic Monitoring of Ecological Environmental Quality and Spatial Pattern Evolution of Urban Agglomeration in Central Yunnan from 2000 to 2020 - Ding Xue; Feng Jingwen; Huang Yuanyuan; Shi Juncheng; Wang Jinliang (Shuitu baochi tongbao)
[Objective] The temporal and spatial variation of ecological environmental quality and its heterogeneity were analyzed in order to provide a scientific basis for the government and relevant departments to formulate ecological environmental protection policies. [Methods] The google earth engine (GEE) platform was used to select Landsat images of central Yunnan Province from 2000 to 2020, and the remote sensing ecological index (RSEI) was extracted year by year. Spatial analysis methods such as hotspot analysis, standard deviation ellipse, and ecological environment gravity center shift were used to explore the temporal and spatial evolution of ecological environmental quality. [Results] ① The overall ecological environmental quality of the central Yunnan urban agglomeration showed a declining trend, and the average RSEI dropped from 0.51 in 2000 to 0.46 in 2020. ② The ecological environmental quality in Central and Eastern Yunnan Province was obviously better than in the western region, except for a few years. Most of the areas with better ecological environmental quality had greater forest coverage. ③ In the past 20 years, the spatial distribution of the ecological environment of the Central Yunnan urban agglomeration showed a north-south direction, and the overall ecological environmental quality of the urban agglomeration showed a certain degree of aggregation. [Conclusion] The deterioration of the ecological environment of the Central Yunnan urban agglomeration was closely related to the rapid expansion of the built-up areas of the urban agglomeration, climatic anomalies, vegetation destruction, and aggravation of soil erosion.